ANALYSIS VALUES OF SOCIAL STRUGGLE IN PASUNG JIWA BY OKKY MADASARI AS POTRAIT OF SOCIAL REALITY (SOCIOLITERARY APPROACH) - Marfuah Unsayaini; Ulfa Tursina; Suryo Ediyono (Universitas Sebelas Maret, 2017)
Pasung Jiwa written by Okky Madasari is a novel that brings social issue of a character who strives for his soul freedom from the feeling of being a prisoner of his own social life. It is a very interesting sociological perspective novel to understand how the characters overcome their social problems. There are a lot of social realities presented in this novel such as bullying case, a case when parents impose their will to their children, sexual harrasment, soul searching, voice to fight against violence and injustices for people who are being marginalized in their social life.